ANALISIS RESIDU PESTISIDA (DIMETHOAT) PADA TANAMAN CABAI MERAH BESAR (Capsicum annum L.) KELOMPOK TANI LESTARI JAYA KABUPATEN KAMPAR - safitri, Hikmah; Sutomo, Sumengen; Zaman, M.Kamali; Muhamadiah, Muhamadiah (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2019)
Pesticides are used in various fields or activities, ranging from household, health, agriculture, besides their benefits, pesticides also have the potential to poison and eradicate other living things, including useful plants and insects, animals and humans. This study aims to determine the pesticide residues with the active ingredient Dimethoat in large red chili plants (Capsicum annum L.). This type of research is an experiment using gas chromathography (GC). The results of this study were pesticide residues on large red chili plants (Capsicum annum L.) above the residual minimum limit (BMR) of 0.05-7 mg / kg in three samples, sample I 127.7504 mg / kg with a percentage of 1.825%, samples II amounting to 30.0019 mg / kg with a percentage of 428% and in Sample III amounting to 58.8435 mg / kg with a percentage of 840%. The conclusion of this study is that farmers use pesticide doses not to use measurable doses, mix the types of pesticides not according to the rules and do the spraying as needed.